2014
DOI: 10.1542/peds.2013-2552
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Expression Profiles in Very Low Birth Weight Infants With Neonatal Sepsis

Abstract: BACKGROUND: Bacterial sepsis is associated with high morbidity and mortality in preterm infants. However, diagnosis of sepsis and identification of the causative agent remains challenging. Our aim was to determine genome-wide expression profiles of very low birth weight (VLBW) infants with and without bacterial sepsis and assess differences. METHODS: This was a prospective observational double-cohort study conducted in VLBW (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 46 publications
10
47
0
Order By: Relevance
“…This justifies direct observations in humans [106]. Most recently, two important genome-wide gene expression studies have provided insights into the molecular pathways activated in newborns with severe infections [88,107]. For instance, on the one hand marked transcriptional alterations in metabolic pathways associated with glucose transport, glycolysis, and cholesterol homeostasis, transport, and metabolism have been detected in newborns during active sepsis [88].…”
Section: Lessons From Neonatal Mouse Modelsmentioning
confidence: 84%
“…This justifies direct observations in humans [106]. Most recently, two important genome-wide gene expression studies have provided insights into the molecular pathways activated in newborns with severe infections [88,107]. For instance, on the one hand marked transcriptional alterations in metabolic pathways associated with glucose transport, glycolysis, and cholesterol homeostasis, transport, and metabolism have been detected in newborns during active sepsis [88].…”
Section: Lessons From Neonatal Mouse Modelsmentioning
confidence: 84%
“…For example, the inclusion of preterm infants with a single blood culture positive for coagulase-negative Staphylococcus (CoNS) may be considered sepsis (33), which is outside of the accepted Centers for Disease Control and Prevention definition for CoNS infection (34). CoNS can be a causative organism of sepsis in neonates but is also considered a frequent contaminant, especially when not supported by documented sustained clinical or laboratory aberrations (33,35). To avoid this important potential limitation in our investigation, we used a mixed (clinical and laboratory) definition for sepsis that incorporated (a) timing of the sepsis event relative to birth, (b) persistence of significant clinical signs for at least 2 d, (c) objective evidence of a systemic inflammatory response and (d) exclusion of all CoNS infections.…”
Section: Discussionmentioning
confidence: 99%
“…A study of VLBW infants with blood culture-proven late-onset sepsis (59% CoNS) identified a 554-gene signature associated with sepsis, with increased expression of the TNF-α network, including matrix metalloproteinase 8 and CD177 among the most commonly up-regulated genes. 465 Elevated matrix metalloproteinase 8 mRNA expression and activity in septic shock correlated with decreased survival and increased organ failure in pediatric patients. Matrix metalloproteinase 8 is a direct activator of NF-κB.…”
Section: Impact Of Systems Biology Approachesmentioning
confidence: 99%